2019
DOI: 10.3390/jrfm12010040
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Affect Income Inequality and Economic Growth in Middle-Income Countries?

Abstract: Income inequality in many middle-income countries has increased at an alarming level. While the time series relationship between income inequality and economic growth has been extensively investigated, the causal and dynamic link between them, particularly for the middle-income countries, has been largely ignored in the current literature. This study was conducted to fill in this gap on two different samples for the period from 1960 to 2014: (i) a full sample of 158 countries; and (ii) a sample of 86 middle-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 52 publications
2
33
0
6
Order By: Relevance
“…restrictions. On the way to implementing such a normative approach, a particularly difficult task is the reliable assessment of the consequences of deepening wage differentiation (e.g., Vo et al, 2019), which will definitely increase in the coming decade of digitalization. A more flexible and pragmatic approach concludes in determining ranges of the sustainable distribution of income and capital specific to certain countries, based on the steadily positive impact of these processes on economic output and its main factors (Cingano, 2014;Dabla-Norris et al, 2015, Taylor et al, 2016.…”
Section: Results Ii: Reality Of the Transition To Sustainable Transformentioning
confidence: 99%
“…restrictions. On the way to implementing such a normative approach, a particularly difficult task is the reliable assessment of the consequences of deepening wage differentiation (e.g., Vo et al, 2019), which will definitely increase in the coming decade of digitalization. A more flexible and pragmatic approach concludes in determining ranges of the sustainable distribution of income and capital specific to certain countries, based on the steadily positive impact of these processes on economic output and its main factors (Cingano, 2014;Dabla-Norris et al, 2015, Taylor et al, 2016.…”
Section: Results Ii: Reality Of the Transition To Sustainable Transformentioning
confidence: 99%
“…The development of derivative markets also causes growth volatility in India, both in the short and long term. Vo et al (2019a) view income inequality in many middle-income countries as having increased at an alarming level. While the time series relationship between income inequality and economic growth has been extensively investigated, the causal and dynamic link between them, particularly for the middle-income countries, has been largely ignored in the current literature.…”
Section: Discussion Of the Review Papersmentioning
confidence: 99%
“…The main study result is that there is a negative and statistically significant connection between economic growth and economic inequality in long-term period, while in short-term period the authors have not found statistically important relation of research variables. By examining the causality of economic growth and economic inequality, Vo Nguyen, Tran and Vo (2018) have established on the example of 158 analyzed countries that two-way causality of the observed variables is present. Additionally, the authors have shown that in the countries with the mean level income, economic inequality negatively reflects on economic growth.…”
Section: H 0 : Cross-section Randommentioning
confidence: 99%